AKAD SALAM, PERMASALAHAN DAN SOLUSINYA - Afria Rachmawati (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
There are several types of financing in banking, one of which is financing with a Salam contract. Where in this Salam contract it is stated that the sale and purchase transaction, in this case the payment occurs at the time of the contract, but the delivery of the goods occurs at a later date with a predetermined time. The problem regarding the salam contract is that so far the salam contract has only been considered suitable for the agricultural industry. The magnitude of the risks contained in the agricultural sector also affects the reluctance of the banking sector to channel working capital to the agricultural sector which is not only based on a salam contract. The lack of Islamic bank financing for the agricultural sector is due to the influence of risks contained in the agricultural business. This explains that in order to reduce business risk or increase the chances of success in the implementation of sharia financing in the agricultural sector, one of the key factors is the need to create an integrated business partnership model between agricultural business actors and sharia banking parties. The form of partnership cooperation can be realized in the pattern of plasma core relationships, subcontracting, general trading, or agribusiness operational cooperation. There is a need for socialization and education related to this contract.